Endocannabinoids in aqueous humour of patients with or without diabetes. Issue 1 (17th February 2020) - Richardson, Patrick; Ortori, Catherine; Barrett, Dave; O'Sullivan, Saoirse; Idris, Iskandar
Abstract : Objective: The primary aim was to determine endocannabinoid (EC) concentrations of 2-arachidonoylglycerol (2-AG), oleoylethanolamine (OEA), palmitoylethanolamine (PEA) and anandamide (AEA) in the aqueous humour of patients, and to investigate any differences in gender and diabetic or ocular disease status. Methods and Analysis: Adult participants (age >18 years) listed for a routine cataract surgery were recruited. For patients with diabetes, results from their most recent retinopathy grading were recorded. A sample of aqueous humour was removed from the anterior chamber of the patients and snap-frozen in liquid nitrogen. Levels of 2-AG, PEA, OEA and AEA were measured by liquid chromatography-tandem mass spectrometry. Results: Aqueous humour samples were taken from 93 patients (female:male=58:35), with a mean age±SD of 72.7±9.5 years. Following gender-specific analysis, the mean aqueous concentration of AEA in female patients without diabetes was significantly higher than in female patients with diabetes (0.20±0.03 nM vs 0.07±0.02 nM, p=0.001). Among female patients with diabetes, the aqueous concentration of 2-AG was higher in those with diabetic retinopathy compared with those with no retinopathy (0.30+0.16 nM vs 0.04±0.01 nM, p=0.0025). The aqueous level of the sum of EC was higher in those with ocular comorbidity (2.49±0.73 vs 1.44±0.17, p=0.0002). Conclusion: There were gender, diabetes status and comorbidity differences in aqueous humour EC levels. Since EC receptors are present in ocular tissues, including the retina (neurons, glia and endothelial cells), differential levels of ECs in the aqueous humour of patients with and without diabetes may provide a novel therapeutic target for diabetic retinopathy.